Perception of environmental management at the hotel sector in São Gabriel city, RS - Saidelles, Ana Paula Fleig; Marinho, Viviana Silveira; Copetti, André Carlos Cruz; Moraes, Beatriz Stoll; Kirchner, Rosane Maria (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
Lately environmental conscience has been growing at the companies, independent of their respective fields. This work has as its objective to know the situation of the environmental management applied at the hotel field in the city of São Gabriel, RS. For this study, was realized a research characterized as: quantitative, describable, explainable. The questionnaire application was realized during the months of September to November of 2014, contemplating 85% of the companies. It was verified that 67% of the administrators of the field have only completed high school, but in the bigger part with a lot of experience at the position they occupy. The majority of the hotel companiesin the city are characterized as small-sized company and familiar administration. When it comesto the environmental damage, it was possible to see that 50% of the interviewed believe that hotels can cause some sort of environmental damage; to compensate, 75% of the enterprisesaffirm to develop any kind of environmental action. It was possible to observe that in the companies where none environmental action is applied, there wasn't interest to adopt these kind of practices having in mind that there isn't any mandatory laws for it. It's hoped that this paper contribute to the entrepreneurs and works of the field, with information and awareness of how important it is to know the possible improvements which can be realized through the application of tools of environmental management, avoiding unnecessary expenses and minimize environment damage.